LncRNA HCG18 affects diabetic cardiomyopathy and its association with miR-9-5p/IGF2R axis - Yuhui Luo; Yi Jiang; Tingting Zhong; Zhenggong Li; Jia He; Xiaoli Li; Kun Cui (Heliyon, 2024)
This paper aimed to investigate the role of lncRNA HCG18 (HCG18) in the progression of diabetic cardiomyopathy (DCM) and potential mechanisms. Streptozocin (STZ) was used to induce DCM model in rats, which was confirmed by blood glucose concentration, body weight, and HE staining. Myocardial apoptosis was detected by TUNEL. H9c2 cardiomyocytes were used to construct cell models of DCM through treatment of high glucose. The results showed that HCG18 was overexpressed in STZ induced DCM rat model and high glucose induced H9c2 cardiomyocytes. Si-HCG18 significantly increased cell viability, reduced cell apoptosis, attenuated activities of myocardial enzymes and enhanced activities of antioxidant enzymes in STZ induced DM model and high glucose induced H9c2 cardiomyocytes, while the results of upregulation of HCG18, in high glucose induced H9c2 cardiomyocytes, were opposite with that of si-HCG18. MiR-9-5p was a target of HCG18, and which was down-regulated in cardiomyocytes of DCM. The overexpression of miR-9-5p could neutralize the high glucose induced cardiomyocyte injury, and the silence of miR-9-5p could reverse the effect of si-HCG18 on high glucose induced cardiomyocytes. MiR-9-5p could directly target to IGF2R, and IGF2R was overexpressed in cardiomyocytes of DCM. Up-regulation of IGF2R can reverse the protective effect of si-HCG18 on cardiomyocytes. Taken together, HCG18 is significantly increased in cardiomyocytes of DCM. Down-regulation of HCG18 can improve cardiomyocyte injury through miR-9-5p/IGF2R axis in DCM.